AKSI MITIGASI DAN INVENTARISASI EMISI PADA SENTRA INDUSTRI GENTENG DI KAMPUNG IKLIM DEMAKAN, MOJOLABAN, KABUPATEN SUKOHARJO - Nida Ulhaq Fil'ardiani; Sunarto; Muhammad Amin Sunarhadi (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
MITIGATION ACTIONS AND EMISSION INVENTORY IN THE ROOF TILE INDUSTRY CENTER IN KAMPUNG IKLIM DEMAKAN, MOJOLABAN, SUKOHARJO REGENCY The roof tile industry still goes through a traditional burning process that risks producing emissions because it uses wood as fuel. Demakan Village, Mojolaban is known as the center of the roof tile industry and has committed to the Climate Village Program to carry out emission mitigation actions. This study aims to determine the characteristics of emissions from the roof tile industry and develop a mitigation action plan in Climate Village Demakan, Mojolaban. The method used is quantitative descriptive analysis through emission inventory according to IPCC 2006 and Delphi analysis with two iterations of questionnaires. The results showed that the total greenhouse gas emissions generated from the roof tile burning was 419.17 tons/year CO2-eq, consisting of 387.88 tons/year CO2, 1.04 tons/year CH4, and 0.014 tons/year N2O. Other emissions are CO at 0.312 tons/year and PM2.5 at 0.4606 tons/year. Emission mitigation action strategy planning includes education or training to the community and planting carbon-absorbing vegetation every 6 months, as well as emission control equipment in the form of a cyclone separator within the next 1-2 years to reduce emissions below quality standards.